Sintered neodymium-iron-boron magnet subjected to grain boundary diffusion treatment
By attaching the diffusion source of heavy rare earth elements on the surface of the sintered NdFeB magnet and optimizing the mass ratio of the grain boundary phase, the problem of poor diffusion effect of heavy rare earth elements on large-thick magnets is solved, efficient diffusion and performance improvement are achieved, while reducing process complexity and cost.
Patent Information
- Application Number
- CN202411895160.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art has poor diffusion effect of heavy rare earth elements on large-thick sintered NdFeB magnets, and the process is complicated, which increases cost and difficulty.
By attaching a diffusion source of heavy rare earth elements to the surface of the sintered NdFeB magnet and performing heat treatment, the grain boundary phase A and grain boundary phase B with a specific mass ratio are formed, and the microstructure of the magnet is optimized to improve the diffusion depth of the heavy rare earth elements.
It realizes a good diffusion effect of heavy rare earth elements on large-thick magnets, ensures uniform distribution of elements inside the magnet, improves the coercive force and squareness of the magnet, and simplifies the process and reduces costs.
Smart Images

Figure CN119889853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth permanent magnet materials, in particular to a sintered NdFeB magnet after grain boundary diffusion treatment. Background Art
[0002] In recent years, the rapid development of new energy vehicles, wind power generation, consumer electronics and other fields has brought about rapid changes in our lives, among which rare earth permanent magnet motors are essential components to promote their development. Sintered NdFeB magnets, known as the "king of magnets", are the key materials for assembling rare earth permanent magnet motors. Sintered NdFeB magnets are widely used in the above fields due to their excellent magnetic properties such as high saturation magnetic induction intensity, high coercive force and high magnetic energy product. However, the actual value of the coercive force of sintered NdFeB magnets is very low, only reaching 12% of its theoretical value. There is still great potential for improving the coercive force, and there is still the possibility of substantial improvement.
[0003] Tb or Dy heavy rare earth elements can be added to 2 Fe 14 B undergoes a substitution reaction to form Tb 2 Fe 14 B or Dy 2 Fe 14 B to significantly increase the coercive force. At present, the grain boundary diffusion process is widely used, which allows the above-mentioned heavy rare earth elements to enter the interior of the magnet from the surface of the magnet along the grain boundary. This can significantly increase the coercive force while reducing the influence of heavy rare earth elements on the remanence and magnetic energy product of the magnet.
[0004] Chinese patent CN102930975B discloses a method for preparing a sintered R-Fe-B magnet. The patent first attaches a layer of Dy or Tb oxide or fluoride coating on the magnet surface, then evaporates potassium or sodium onto the coating and performs heat treatment together. By using potassium or sodium as a reducing agent to replace Dy or Tb at a lower temperature, the speed of Dy and Tb infiltration can be greatly improved. Chinese patent CN104388952B discloses a method for accelerating the diffusion of Dy / Tb adhesion layer on the surface of sintered NdFeB magnets. After attaching Dy / Tb elements to the surface of sintered NdFeB magnets, the patent simultaneously performs heat treatment under pressure to accelerate the diffusion of Dy / Tb elements in the grain boundaries of sintered NdFeB magnets, thereby obtaining high coercive force magnets. The above two patents are indeed helpful in increasing the diffusion depth of heavy rare earth elements, but the thickness of the magnets is 4mm, and the improvement effect on thick magnets is limited and the process is complicated.
[0005] The problem is that the existing invention helps to increase the diffusion depth of heavy rare earth elements, but the thickness of most magnets is less than 10 mm, and the improvement effect is limited on thick magnets. In addition, the process of the existing invention is complicated, adding a large number of steps and costs. Summary of the invention
[0006] In view of the above-mentioned shortcomings, the present invention proposes a sintered NdFeB magnet after grain boundary diffusion treatment, which solves the problem of poor diffusion effect of heavy rare earth elements in thick magnets. The magnet matrix and diffusion both use existing processes, so that good diffusion effect can be achieved in thick magnets with excellent performance and good squareness.
[0007] To achieve the above object, the present invention provides the following technical solution: a sintered NdFeB magnet after grain boundary diffusion treatment, the sintered NdFeB magnet comprising main phase grains and grain boundary phases A and B with different contrast differences, the grain boundary phases A and B both contain R element and M element, the R element is selected from at least one element of Tb and Dy, and the mass ratio of the R element satisfies:
[0008] 1<R1 / R3<100;
[0009] 1<R2 / R4<200;
[0010] 1<R1 / R2<10;
[0011] The M element is selected from at least one element of Al, Cu, Ga, and Fe, and the mass ratio of the M element satisfies:
[0012] 1<M1 / M3<30;
[0013] 1<M2 / M4<20;
[0014] 0.1<M1 / M2<1;
[0015] R1 and M1 are the mass ratios of R and M elements in the grain boundary phase A within d1 from the surface of the sintered NdFeB magnet, R2 and M2 are the mass ratios of R and M elements in the grain boundary phase B within d1 from the surface of the sintered NdFeB magnet, R3 and M3 are the mass ratios of R and M elements in the grain boundary phase A within d2 from the surface of the sintered NdFeB magnet, R4 and M4 are the mass ratios of R and M elements in the grain boundary phase B within d2 from the surface of the sintered NdFeB magnet.
[0016] As an improvement, d1 is 0 to 100 μm from the surface of the NdFeB magnet, and d2 is 100 to 500 μm from the surface of the NdFeB magnet.
[0017] As an improvement, the sum of the areas of the main phase grains, the sum of the areas of the grain boundary phase A, and the sum of the areas of the grain boundary phase B all satisfy:
[0018] 0.02≤(S2+S3) / (S1+S2+S3)≤0.08;
[0019] 0.1≤S3 / (S2+S3)≤0.5;
[0020] S1+S2+S3=1
[0021] S1 is the total area of the main phase grains in the sintered NdFeB magnet, S2 is the total area of the grain boundary phase A in the cross section of the sintered NdFeB magnet, and S3 is the total area of the grain boundary phase B in the cross section of the sintered NdFeB magnet.
[0022] As an improvement, the main phase grain contrast is dark gray, the grain boundary phase A contrast is white, and the grain boundary phase B contrast is light gray.
[0023] As an improvement, the grain boundary diffusion is to attach a diffusion source containing at least one heavy rare earth element Dy or Tb to the surface of the NdFeB magnet to form an attachment layer and then perform heat treatment.
[0024] As an improvement, the attachment method includes but is not limited to printing, evaporation, spraying, and magnetron sputtering.
[0025] As an improvement, the sintered NdFeB magnet includes a magnet matrix and an adhesion layer attached to the surface of the magnet matrix, the diffusion direction of the adhesion layer is the thickness direction of the magnet matrix, and the thickness of the magnet matrix is 1 to 30 mm.
[0026] Preferably, 1<R1 / R3<30; 1<R2 / R4<60; 1<R1 / R2<5.
[0027] Preferably, 1<M1 / M3<3; 1<M2 / M4<3; 0.1<M1 / M2<1.
[0028] The advantages of the present invention are:
[0029] (1) The present invention can achieve good diffusion effect in thick magnets. The diffusion source components can be effectively diffused along the thickness direction of the magnet matrix, ensuring uniform distribution of elements inside the thick magnet. This excellent diffusion effect enables the magnet to maintain stable performance at different thicknesses.
[0030] (2) The preparation and diffusion process of the magnet of the present invention both use existing conventional processes, without increasing costs and other steps, thereby reducing the production cost and difficulty in the production process. In addition, the selection of multiple attachment methods such as printing, evaporation, spraying, and magnetron sputtering also increases the flexibility and diversity of preparation.
[0031] (3) The present invention significantly optimizes the microstructure of the magnet through reasonable design of grain boundary phase A and grain boundary phase B. Parameters such as the area ratio and element distribution of grain boundary phase A and grain boundary phase B are carefully controlled to ensure that the magnet has good squareness while maintaining high coercive force. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0033] Figure 1 It is a schematic diagram of an enlarged cross section of a sintered NdFeB magnet after grain boundary diffusion treatment;
[0034] Figure 2 This is a scanning electron microscope image of a cross section of the magnet of Example 1 at a distance of 20 μm from the surface;
[0035] Figure 3 This is a scanning electron microscope image of a cross section of the magnet of Example 1 at a distance of 300 μm from the surface;
[0036] Figure 4 This is a scanning electron microscope image of a cross section of the magnet of Example 4 at a distance of 20 μm from the surface;
[0037] Figure 5 This is a scanning electron microscope image of a cross section of the magnet of Example 4 at a distance of 300 μm from the surface;
[0038] Figure 6 This is a scanning electron microscope image of a cross section of the magnet of Example 7 at a distance of 20 μm from the surface;
[0039] Figure 7 This is a scanning electron microscope image of the cross section of the magnet of Example 7 at a distance of 100 μm from the surface. DETAILED DESCRIPTION
[0040] like Figures 1 to 7 As shown, a sintered NdFeB magnet after grain boundary diffusion treatment, the sintered NdFeB magnet includes main phase grains and grain boundary phases A and B with different contrast differences, the grain boundary phases A and B both contain R element and M element, the R element is selected from at least one element of Tb and Dy, and the mass ratio of the R element satisfies:
[0041] 1<R1 / R3<100, preferably, 1<R1 / R3<30;
[0042] 1<R2 / R4<200, preferably, 1<R2 / R4<60;
[0043] 1<R1 / R2<10, preferably, 1<R1 / R2<5;
[0044] The M element is selected from at least one element of Al, Cu, Ga, and Fe, and the mass ratio of the M element satisfies:
[0045] 1<M1 / M3<30, preferably, 1<M1 / M3<3;
[0046] 1<M2 / M4<20, preferably, 1<M2 / M4<3;
[0047] 0.1<M1 / M2<1;
[0048] R1 and M1 are the mass ratios of R and M elements in the grain boundary phase A within d1 from the surface of the sintered NdFeB magnet, R2 and M2 are the mass ratios of R and M elements in the grain boundary phase B within d1 from the surface of the sintered NdFeB magnet, R3 and M3 are the mass ratios of R and M elements in the grain boundary phase A within d2 from the surface of the sintered NdFeB magnet, R4 and M4 are the mass ratios of R and M elements in the grain boundary phase B within d2 from the surface of the sintered NdFeB magnet.
[0049] The NdFeB magnet prepared by the present invention is mainly composed of Nd 2 Fe 14 The B main phase and the grain boundary phase surrounded by multiple main phase particles are composed, 3 or more main phase particles surround to form a triangular grain boundary phase, and 2 main phase particles constitute a two-grain grain boundary phase. In the present invention, the grain boundary phase B is mainly distributed in the triangular grain boundary phase, a few are distributed in the two-grain grain boundary phase, and the grain boundary phases other than the grain boundary phase B are all grain boundary phases A.
[0050] d1 is 0 to 100 μm from the surface of the NdFeB magnet, and d2 is 100 to 500 μm from the surface of the NdFeB magnet.
[0051] The sum of the areas of the main phase grains, the sum of the areas of the grain boundary phase A, and the sum of the areas of the grain boundary phase B all satisfy:
[0052] 0.02≤(S2+S3) / (S1+S2+S3)≤0.08;
[0053] 0.1≤S3 / (S2+S3)≤0.5;
[0054] S1+S2+S3=1
[0055] S1 is the total area of the main phase grains in the sintered NdFeB magnet, S2 is the total area of the grain boundary phase A in the cross section of the sintered NdFeB magnet, and S3 is the total area of the grain boundary phase B in the cross section of the sintered NdFeB magnet.
[0056] The contrast of the main phase grains is dark gray, the contrast of the grain boundary phase A is white, and the contrast of the grain boundary phase B is light gray.
[0057] Grain boundary diffusion is to attach a diffusion source containing at least one heavy rare earth element Dy and Tb to the surface of the NdFeB magnet to form an adhesion layer and then perform heat treatment. Preferably, during the grain boundary diffusion process, heavy rare earth elements such as Tb and Dy enter the grain boundary phase, and a part of them contacts the surface of the main phase particles to form a heavy rare earth shell layer, which gradually becomes thinner as the diffusion depth increases, and another part of them continuously enters the interior of the magnet along the grain boundary to repeat the replacement reaction. Trace elements such as Al, Cu, and Ga improve the wettability of the grain boundary phase and enter the interior of the magnet along the grain boundary phase. After diffusion, the main element of the grain boundary phase in the magnet is Nd, and a small amount of heavy rare earth elements such as Tb and Dy are concentrated in the grain boundary phase A, and other trace elements such as Al, Cu, and Ga are dispersed in the grain boundary phase.
[0058] The attachment methods include, but are not limited to, printing, evaporation, spraying, and magnetron sputtering.
[0059] The sintered NdFeB magnet comprises a magnet matrix and an adhesion layer attached to the surface of the magnet matrix. The diffusion direction of the adhesion layer is the thickness direction of the magnet matrix. The thickness of the magnet matrix is 1 to 30 mm.
[0060] The following examples describe the steps involved in grain boundary diffusion treatment of a sintered NdFeB magnet made by a conventional method using different terbium-containing diffusion sources, magnetic property test results, and R and M element analysis results.
[0061] Embodiment 1
[0062] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum to obtain R1 content of 43.91%, R2 content of 14.37%, R3 content of 0.45%, R4 content of 0.08%, M1 content of 9.41%, M2 content of 9.60%, M3 content of 1.69%, and M4 content of 1.71%. The ratio relationship is shown in Table 1, R1 / R3 is 97.58, R2 / R4 is 179.63, R1 / R2 is 3.06, M1 / M3 is 5.57, M2 / M4 is 5.61, and M1 / M2 is 0.98. The preparation steps are as follows:
[0063] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×20mm cuboid with a thickness of 20mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0064] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0065] S3: Tb-H diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0066] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0067] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 300μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0068] After the sintered NdFeB magnet was subjected to grain boundary diffusion treatment by the diffusion source, as shown in Table 2, the magnetic properties results showed that the remanence was 14.39 kGs, the intrinsic coercive force was 22.97 kOe, and the squareness was 0.959. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.051, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.008, (S2+S3) / (S1+S2+S3) was 0.059, and S3 / (S2+S3) was 0.136.
[0069] The scanning electron microscope image of the cross section at 20 μm from the magnet surface is shown in Figure 2 As shown in the scanning electron microscope image of the cross section at 300 μm from the magnet surface, Figure 3 As shown in the figure, after the Tb-H diffusion source grain boundary diffusion treatment, the key performance indicator of the magnet, the coercive force, has been improved, and the squareness of the magnet has also remained relatively good. The R1 / R3 value is 97.58, indicating that the heavy rare earth element terbium can still achieve a good diffusion effect at a depth of 300μm. The area of the grain boundary phase B accounts for 0.136 of the total grain boundary phase area, indicating that the grain boundary phase B formed after the Tb-H diffusion source grain boundary diffusion is relatively small, resulting in a small amount of enrichment of the heavy rare earth element terbium in the surface grain boundary phase B, and the R2 / R4 value is 179.63. The similar results of M1 / M3 and M2 / M4 indicate that the grain boundary phases A and B after the Tb-H diffusion source grain boundary diffusion have no effect on the diffusion of Al, Cu, Ga, and Fe elements.
[0070] Embodiment 2
[0071] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum and has R1 content of 30.13%, R2 content of 10.43%, R3 content of 0.72%, R4 content of 0.11%, M1 content of 13.28%, M2 content of 15.67%, M3 content of 2.42%, and M4 content of 3.70%. The ratio relationship is shown in Table 1, R1 / R3 is 41.85, R2 / R4 is 94.82, R1 / R2 is 2.89, M1 / M3 is 5.49, M2 / M4 is 4.24, and M1 / M2 is 0.85. The preparation steps are as follows:
[0072] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×20mm cuboid with a thickness of 20mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0073] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0074] S3: Tb-Cu diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0075] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0076] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 300μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0077] After the sintered NdFeB magnet was subjected to grain boundary diffusion treatment by the diffusion source, as shown in Table 2, the magnetic properties results showed that the remanence was 14.27 kGs, the intrinsic coercive force was 24.80 kOe, and the squareness was 0.965. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.04, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.013, (S2+S3) / (S1+S2+S3) was 0.053, and S3 / (S2+S3) was 0.245.
[0078] It can be seen from the results that after the Tb-Cu diffusion source grain boundary diffusion treatment, the R1 / R3 and R2 / R4 results perform well. Since the Cu element participates in the diffusion process, it not only improves the diffusion effect of the heavy rare earth element terbium, but also promotes the formation of grain boundary phase B and optimizes the M1 / M2 and M2 / M4 results, improves the diffusion effect of Al, Cu, Ga, and Fe elements in the grain boundary phase B, and the coercive force is therefore increased to 24.80kOe. The squareness of the magnet is also maintained relatively well.
[0079] Embodiment 3
[0080] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum and has R1 content of 23.43%, R2 content of 10.17%, R3 content of 1.01%, R4 content of 0.17%, M1 content of 15.46%, M2 content of 17.93%, M3 content of 4.19%, and M4 content of 5.01%. The ratio relationship is shown in Table 1, R1 / R3 is 23.20, R2 / R4 is 59.82, R1 / R2 is 2.30, M1 / M3 is 3.69, M2 / M4 is 3.58, and M1 / M2 is 0.86. The preparation steps are as follows:
[0081] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×20mm cuboid with a thickness of 20mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0082] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0083] S3: PrTbCuGa diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0084] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0085] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 300μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0086] After the sintered NdFeB magnet was treated with grain boundary diffusion by the diffusion source, as shown in Table 2, the magnetic properties showed that the remanence was 14.21 kGs, the intrinsic coercive force was 25.22 kOe, and the squareness was 0.969. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.032, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.018, (S2+S3) / (S1+S2+S3) was 0.050, and S3 / (S2+S3) was 0.360.
[0087] It can be seen from the results that when R1 / R3, R2 / R4, and R1 / R2 are within the preferred range after grain boundary diffusion using the PrTbCuGa diffusion source, the heavy rare earth element terbium has a good diffusion effect, the coercive force of the magnet is significantly improved, reaching 25.22kOe, and the squareness of the magnet is also maintained well. The fact that M1 / M3 and M2 / M4 are close to the preferred range shows that the participation of Pr, Cu, and Ga elements in the diffusion process has a greater impact on the diffusion effect of Al, Cu, Ga, and Fe elements, and increases the diffusion depth. Pr and Ga elements further optimize the grain boundary phase. This embodiment can achieve a good diffusion effect in a thick magnet, and the diffusion source can effectively diffuse along the thickness direction of the magnet matrix, so that the elements inside the thick magnet are evenly distributed.
[0088] Embodiment 4
[0089] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum to obtain R1 content of 15.93%, R2 content of 8.43%, R3 content of 1.28%, R4 content of 0.21%, M1 content of 17.33%, M2 content of 24.70%, M3 content of 9.56%, and M4 content of 19.63%. The ratio relationship is shown in Table 1, R1 / R3 is 12.45, R2 / R4 is 40.14, R1 / R2 is 1.89, M1 / M3 is 1.81, M2 / M4 is 1.26, and M1 / M2 is 0.70. The preparation steps are as follows:
[0090] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×20mm cuboid with a thickness of 20mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0091] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0092] S3: PrTbCuGaFe diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0093] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0094] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 300μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0095] After the sintered NdFeB magnet was treated with grain boundary diffusion by the diffusion source, as shown in Table 2, the magnetic properties showed that the remanence was 14.17 kGs, the intrinsic coercive force was 25.49 kOe, and the squareness was 0.978. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.031, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.021, (S2+S3) / (S1+S2+S3) was 0.052, and S3 / (S2+S3) was 0.404.
[0096] The scanning electron microscope image of the cross section at 20 μm from the magnet surface is shown in Figure 4 As shown in the scanning electron microscope image of the cross section at 300 μm from the magnet surface, Figure 5As shown, after grain boundary diffusion using the PrTbCuGaFe diffusion source, when R1 / R3, R2 / R4, M1 / M3, and M2 / M4 are all within the preferred range, the addition of Pr, Cu, Ga, and Fe elements not only improves the diffusion effect of Tb, Al, Cu, and Ga elements in the magnet and increases the diffusion depth, but also optimizes the distribution of grain boundary phases A and B. This embodiment can achieve a better diffusion effect in a thick magnet, greatly improves the coercive force of the magnet while ensuring the squareness, and the diffusion source can effectively diffuse along the thickness direction of the magnet matrix, so that the elements inside the thick magnet are evenly distributed.
[0097] Embodiment 5
[0098] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum to obtain R1 content of 16.12%, R2 content of 9.19%, R3 content of 1.60%, R4 content of 0.32%, M1 content of 17.27%, M2 content of 24.22%, M3 content of 10.02%, and M4 content of 20.30%. The ratio relationship is shown in Table 1, R1 / R3 is 10.08, R2 / R4 is 28.72, R1 / R2 is 1.75, M1 / M3 is 1.72, M2 / M4 is 1.19, and M1 / M2 is 0.71. The preparation steps are as follows:
[0099] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×10mm cuboid with a thickness of 10mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0100] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0101] S3: PrTbCuGaFe diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0102] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0103] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 300μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0104] After the sintered NdFeB magnet was subjected to grain boundary diffusion treatment by the diffusion source, as shown in Table 2, the magnetic properties results showed that the remanence was 14.20 kGs, the intrinsic coercive force was 25.53 kOe, and the squareness was 0.983. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.028, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.025, (S2+S3) / (S1+S2+S3) was 0.053, and S3 / (S2+S3) was 0.472.
[0105] Using PrTbCuGaFe diffusion source for grain boundary diffusion, the diffusion effect is more excellent when the magnet thickness is 10mm, R1 / R3, R2 / R4, M1 / M3, M2 / M4 are also within the preferred range, and the coercive force of this embodiment reaches the best 25.53kOe. When the thickness of the magnet becomes thinner, the diffusion source can still achieve a better diffusion effect in the magnet, and the diffusion source can effectively diffuse along the thickness direction of the magnet matrix, so that the elements inside the magnet are more evenly distributed.
[0106] Embodiment 6
[0107] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum to obtain R1 content of 16.09%, R2 content of 8.97%, R3 content of 0.91%, R4 content of 0.15%, M1 content of 17.19%, M2 content of 24.26%, M3 content of 9.87%, and M4 content of 20.98%. The ratio relationship is shown in Table 1, R1 / R3 is 17.68, R2 / R4 is 59.80, R1 / R2 is 1.79, M1 / M3 is 1.74, M2 / M4 is 1.16, and M1 / M2 is 0.71. The preparation steps are as follows:
[0108] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×30mm cuboid with a thickness of 30mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0109] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0110] S3: PrTbCuGaFe diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0111] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0112] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 300μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0113] After the sintered NdFeB magnet was subjected to grain boundary diffusion treatment by the diffusion source, as shown in Table 2, the magnetic properties results showed that the remanence was 14.25 kGs, the intrinsic coercive force was 25.41 kOe, and the squareness was 0.968. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.036, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.017, (S2+S3) / (S1+S2+S3) was 0.053, and S3 / (S2+S3) was 0.321.
[0114] Using PrTbCuGaFe diffusion source grain boundary diffusion, when the magnet thickness is 30mm, it can still show excellent diffusion effect, R1 / R3, R2 / R4, M1 / M3, M2 / M4 are also within the preferred range, and the coercive force can still reach 25.41kOe. This embodiment can still achieve a good diffusion effect on a thicker magnet, and the diffusion source components can be effectively diffused along the thickness direction of the magnet matrix, so that the elements inside the thicker magnet are well and evenly distributed.
[0115] Embodiment 7
[0116] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum to obtain R1 content of 16.06%, R2 content of 8.91%, R3 content of 6.32%, R4 content of 0.40%, M1 content of 17.37%, M2 content of 24.49%, M3 content of 13.72%, and M4 content of 23.28%. The ratio relationship is shown in Table 1, R1 / R3 is 2.54, R2 / R4 is 22.28, R1 / R2 is 1.80, M1 / M3 is 1.27, M2 / M4 is 1.05, and M1 / M2 is 0.71. The preparation steps are as follows:
[0117] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×20mm cuboid with a thickness of 20mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0118] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0119] S3: PrTbCuGaFe diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0120] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0121] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 100μm away from the magnet surface respectively, and use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0122] After the sintered NdFeB magnet was subjected to grain boundary diffusion treatment by the diffusion source, as shown in Table 2, the magnetic properties results showed that the remanence was 14.15 kGs, the intrinsic coercive force was 25.51 kOe, and the squareness was 0.973. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.03, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.018, (S2+S3) / (S1+S2+S3) was 0.048, and S3 / (S2+S3) was 0.375.
[0123] The scanning electron microscope image of the cross section at 20 μm from the magnet surface is shown in Figure 6 As shown in the scanning electron microscope image of the cross section at 100 μm from the magnet surface Figure 7 As shown, when using PrTbCuGaFe diffusion source to diffuse grain boundaries on a 20mm thick magnet, when selecting a distance of 100μm from the magnet surface, it is found that R1 / R3, R2 / R4, R1 / R2 are at lower values within the preferred range, and M1 / M3, M2 / M4, M1 / M2 are also at lower values within the preferred range. This embodiment can achieve a good diffusion effect on thick magnets, greatly improve the coercive force of the magnet while ensuring the squareness, and the diffusion source can effectively diffuse along the thickness direction of the magnet matrix, so that the elements inside the thick magnet are evenly distributed.
[0124] Embodiment 8
[0125] In grain boundary phase A and grain boundary phase B, R is the mass ratio of Tb element, and M is the sum of the mass ratios of Al, Cu, Ga, and Fe elements. The magnet is analyzed by energy spectrum and has R1 content of 15.89%, R2 content of 9.00%, R3 content of 0.17%, R4 content of 0.06%, M1 content of 17.45%, M2 content of 24.32%, M3 content of 8.74%, and M4 content of 18.54%. The ratio relationship is shown in Table 1, R1 / R3 is 93.47, R2 / R4 is 150.00, R1 / R2 is 1.77, M1 / M3 is 2.00, M2 / M4 is 1.31, and M1 / M2 is 0.72. The preparation steps are as follows:
[0126] S1: A matrix with a composition of 29.9wt.% PrNd, 0.97wt.% B, and the remainder Fe and other trace elements is prepared by a conventional method, and the matrix is machined and cut into a 12×12×20mm cuboid with a thickness of 20mm, and the thickness direction is the orientation direction of the NdFeB magnet;
[0127] S2: The magnet is placed in 4% nitric acid alcohol for ultrasonic cleaning for 2 minutes to clean the oil on the surface of the magnet, and then placed in anhydrous ethanol for ultrasonic cleaning for 1 minute to clean the residual nitric acid alcohol, and then dried to remove the anhydrous ethanol;
[0128] S3: PrTbCuGaFe diffusion source powder is prepared into ink by conventional methods, and the diffusion source is attached to two surfaces in the orientation direction of the substrate by screen printing, wherein the mass of terbium is 0.3% of the mass of the magnet;
[0129] S4: After drying, put it into a molybdenum box for diffusion heat treatment, the diffusion temperature is 900°C, the diffusion time is 30h, and then it is cooled to room temperature and then tempered, the tempering temperature is 500°C, the tempering time is 5h, and then it is taken out after cooling to room temperature;
[0130] S5: Use a permanent magnet material measuring instrument to test the magnetic properties of the magnet, and then use a scanning electron microscope and an energy spectrometer to analyze the grain boundary phases A and B at 20μm and 500μm away from the magnet surface respectively. Use Photoshop software to extract the pixel points of different grain boundary phases in the scanning electron microscope image and calculate the area of different grain boundary phases.
[0131] After the sintered NdFeB magnet was subjected to grain boundary diffusion treatment by the diffusion source, as shown in Table 2, the magnetic properties results showed that the remanence was 14.20 kGs, the intrinsic coercive force was 25.48 kOe, and the squareness was 0.975. As shown in Table 3, the total area S2 of the grain boundary phase A in the cross section of the sintered NdFeB magnet was 0.028, the total area S3 of the grain boundary phase B in the cross section of the sintered NdFeB magnet was 0.021, (S2+S3) / (S1+S2+S3) was 0.049, and S3 / (S2+S3) was 0.429.
[0132] When using the PrTbCuGaFe diffusion source for grain boundary diffusion on a 20mm thick magnet, it is found that M1 / M3, M2 / M4, and M1 / M2 are also within the preferred range when the distance from the magnet surface is 500μm, but the values of R1 / R3 and R2 / R4 are relatively large, indicating that the diffusion effect of the heavy rare earth element Tb at 500μm is not as good as that of Al, Cu, Ga, and Fe elements. Al, Cu, Ga, and Fe elements have a good diffusion effect and do not affect the performance results of the magnet. This embodiment can achieve a good diffusion effect in a thick magnet, greatly improve the coercive force of the magnet while ensuring the squareness, and the diffusion source can effectively diffuse along the thickness direction of the magnet matrix, so that the elements inside the thick magnet are evenly distributed.
[0133] Table 1 Results of the relationship between the mass ratios of R and M elements in Example 1 to Example 8
[0134] name R1 / R3 M1 / M3 R2 / R4 M2 / M4 R1 / R2 M1 / M2 Example 1 97.58 5.57 179.63 5.61 3.06 0.98 Example 2 41.85 5.49 94.82 4.24 2.89 0.85 Example 3 23.20 3.69 59.82 3.58 2.30 0.86 Example 4 12.45 1.81 40.14 1.26 1.89 0.70 Example 5 10.08 1.72 28.72 1.19 1.75 0.71 Example 6 17.68 1.74 59.80 1.16 1.79 0.71 Example 7 2.54 1.27 22.28 1.05 1.80 0.71 Example 8 93.47 2.00 150.00 1.31 1.77 0.72
[0135] Table 2 Magnetic properties results of Examples 1 to 8
[0136]
[0137]
[0138] Table 3 Area results of grain boundary phases A and B in Examples 1 to 8
[0139] name S2 S3 (S2+S3) / (S1+S2+S3) S3 / (S2+S3) Example 1 0.051 0.008 0.059 0.136 Example 2 0.040 0.013 0.053 0.245 Example 3 0.032 0.018 0.050 0.360 Example 4 0.031 0.021 0.052 0.404 Example 5 0.028 0.025 0.053 0.472 Example 6 0.036 0.017 0.053 0.321 Example 7 0.030 0.018 0.048 0.375 Example 8 0.028 0.021 0.049 0.429
[0140] It can be seen from the test results of Examples 1 to 8 that the sintered NdFeB magnet of the present invention, whether using terbium hydride or terbium-containing alloy diffusion source, can show excellent performance in large thickness, and the squareness is good enough to meet the use requirements.
[0141] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A sintered NdFeB magnet after grain boundary diffusion treatment, characterized in that: The sintered NdFeB magnet comprises main phase grains and grain boundary phases A and B with different contrast differences, wherein both the grain boundary phases A and B contain R elements and M elements, wherein the R element is selected from at least one of Tb and Dy, and the mass ratio of the R element satisfies: 1<R1 / R3<100; 1<R2 / R4<200; 1<R1 / R2<10; The M element is selected from at least one element of Al, Cu, Ga, and Fe, and the mass ratio of the M element satisfies: 1<M1 / M3<30; 1<M2 / M4<20; 0.1<M1 / M2<1; The R1 and M1 are respectively the mass ratios of the R and M elements in the grain boundary phase A within d1 from the surface of the sintered NdFeB magnet, the R2 and M2 are respectively the mass ratios of the R and M elements in the grain boundary phase B within d1 from the surface of the sintered NdFeB magnet, the R3 and M3 are respectively the mass ratios of the R and M elements in the grain boundary phase A within d2 from the surface of the sintered NdFeB magnet, and the R4 and M4 are respectively the mass ratios of the R and M elements in the grain boundary phase B within d2 from the surface of the sintered NdFeB magnet.
2. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 1, characterized in that: The distance d1 is 0 to 100 μm from the surface of the NdFeB magnet, and the distance d2 is 100 to 500 μm from the surface of the NdFeB magnet.
3. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 1, characterized in that: The sum of the areas of the main phase grains, the sum of the areas of the grain boundary phase A and the sum of the areas of the grain boundary phase B simultaneously satisfy: 0.02≤(S2+S3) / (S1+S2+S3)≤0.08; 0.1≤S3 / (S2+S3)≤0.5; S1+S2+S3=1 The S1 is the total area of the main phase grains in the sintered NdFeB magnet, the S2 is the total area of the grain boundary phase A in the cross section of the sintered NdFeB magnet, and the S3 is the total area of the grain boundary phase B in the cross section of the sintered NdFeB magnet.
4. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 1, characterized in that: The main phase grain contrast is dark gray, the grain boundary phase A contrast is white, and the grain boundary phase B contrast is light gray.
5. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 1, characterized in that: The grain boundary diffusion is to attach a diffusion source containing at least one heavy rare earth element Dy or Tb to the surface of the NdFeB magnet to form an attachment layer and then perform heat treatment.
6. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 5, characterized in that: The attachment method includes but is not limited to printing, evaporation, spraying, and magnetron sputtering.
7. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 5, characterized in that: The sintered NdFeB magnet comprises a magnet matrix and an adhesion layer attached to the surface of the magnet matrix. The diffusion direction of the adhesion layer is the thickness direction of the magnet matrix. The thickness of the magnet matrix is 1 to 30 mm.
8. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 1, characterized in that: The above-mentioned 1<R1 / R3<30; 1<R2 / R4<60; 1<R1 / R2<5.
9. The sintered NdFeB magnet after grain boundary diffusion treatment according to claim 1, characterized in that: The above-mentioned 1<M1 / M3<3; 1<M2 / M4<3; 0.1<M1 / M2<1.
Citation Information
Patent Citations
A method for preparing R-Fe-B sintered magnets
CN102930975B
A method of accelerating the diffusion and penetration of dy / tb adhesion layer on the surface of sintered NdFeB magnet
CN104388952B